Quantification of mixture composition, liquid-phase fraction and - temperature in transcritical sprays - Peter, Andreas; Rieß, Sebastian; Wensing, Michael; Braeuer, Andreas S.; Klima, Tobias C. (Journal of Supercritical Fluids, 2020)
How do fuel and air mix, if a liquid fuel is injected into an environment featuring pressure and temperature that exceed the critical pressure and the critical temperature of the fuel? It is subject of current discussion on whether and if so when, the fuel/air-mixture becomes supercritical or not. We here report experimental data comprising three mixture properties that are relevant for the current debate, all spatially and temporally resolved throughout the spray and injection event: The overall composition of the fuel/air-mixture, the liquid fraction of the fuel/air-mixture, and the temperature of the liquid phase. To this end, we applied Raman spectroscopy and gave special attention to the signature of the Raman OH-band of ethanol, which we used as fuel. Its signature is connected to the development of a hydrogen bonded network between the ethanol molecules and thus extremely sensitive to thermodynamic state and temperature. Measurements were carried out in a high-pressure, high-temperature combustion vessel in a pressure range of 3−8 MPa and a temperature range of 573−923 K. For the highest set temperature we found ethanol in liquid-like mixtures that exceeded the mixture critical temperature. This is an indication of the existence of a single-phase mixing path.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Diesel; Ethanol; Liquid fraction; Liquid phase; Raman spectroscopy; Spray; Temperature; Transcritical